Perspectives on the Discourse of Islamization of Education - Ahmed, Mohammad Kaosar (American Journal of Humanities and Social Sciences, 2014)
<!--[if gte mso 9]> <![endif]--> Islamic educationists and thinkers put forward that the concepts of education should be anchored in the strengths of akidah (faith). They prescribe that faith and knowledge should be integrated to ensure that the individuals can be guided to be the khalifatullah (Allah’s vicegerent). Knowledge should be relied to permanent sources and not to relative ones to ensure that its existence is in line with the ultimate and permanent faith and beliefs. Men’s intellectual abilities are closely linked to the Creator. Educational system which is not aqidah-oriented will produce imbalanced and less harmonious societies. The holding of the First World Conference on Muslim Education in 1977 was significant event that in fact boost up the resurgence of education in Muslim societies. The fundamental purpose of the conference was to bring back into the Muslim education the Islamic vision. At the background of the historic event, there was a realization among Muslim scholars of the crisis that had beset their education over time. Examining the relevant literature, this paper attempts to present various perspectives on Islamization of Education including the crisis of the Muslim mind, the major findings of the Makkah World Conference, the neutrality of modern knowledge, the process of Islamization and teacher education. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[endif] --><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]-->